2019
DOI: 10.1016/j.chembiol.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Modification and Regulation of the Nuclear Receptor Nurr1 by a Dopamine Metabolite

Abstract: Highlights d The dopamine metabolite 5,6-dihydroxyindole (DHI) binds directly to Nurr1 d DHI forms a covalent adduct with Nurr1, reacting as the indolequinone with Cys566 d The Nurr1-metabolite structure reveals a previously unreported ligand-binding pocket d DHI stimulates the transcription of Nurr1 target genes underlying dopamine homeostasis

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 112 publications
1
81
0
2
Order By: Relevance
“…We also found that the mutations in the first exon of NURR1 gene (−291Tdel and −245T → G) are associated with human familial PD (Le et al, 2003). Therefore, Nurr1 has been regarded as a potential susceptibility gene for PD (Bruning et al, 2019). This gene may also serve as a master downstream molecular target for α-SYN-induced neuron toxicity (Decressac et al, 2012).…”
Section: Introductionmentioning
confidence: 81%
“…We also found that the mutations in the first exon of NURR1 gene (−291Tdel and −245T → G) are associated with human familial PD (Le et al, 2003). Therefore, Nurr1 has been regarded as a potential susceptibility gene for PD (Bruning et al, 2019). This gene may also serve as a master downstream molecular target for α-SYN-induced neuron toxicity (Decressac et al, 2012).…”
Section: Introductionmentioning
confidence: 81%
“…Several compounds have been reported in the literature to interact with the Nurr1 LBD. Unsaturated fatty acids, amodiaquine, and chloroquine appear to bind to the Nurr1 orthosteric ligand-binding pocket (4,5,11), whereas the endogenous dopamine metabolite 5,6-dihydroxyindole (DHI) covalently binds to noncanonical site via covalent attachment to a surface-exposed cysteine residue in the Nurr1 LBD (7).…”
Section: Discussionmentioning
confidence: 99%
“…Crystal structures of the Nur77 and Nurr1 ligand-binding domains (LBDs) show a collapsed orthosteric pocket that is filled with residues containing bulky hydrophobic sidechains suggesting these receptors may function independent of binding ligand within an orthosteric pocket (2,3). Furthermore, contributing to their status as orphan receptors, it remains unclear if the NR4As are regulated by binding physiological or endogenous ligands, although unsaturated fatty acids (4)(5)(6) and dopamine metabolites (7) have been shown to interaction with the Nur77 and/or Nurr1 LBDs.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated the protective role and correlation of Nurr1 in cell death by oxidative stress, but the detailed molecular mechanism of Nurr1 against oxidative stress remains unclear [17,19,20,60,[81][82][83]. Interestingly, a contemporary study reporting the direct binding of dopamine metabolite on Nurr1 and its stimulation of Nurr1 activity may provide an evidence for mechanism underlying the role of Nurr1 in sensing and responding the oxidative stress [84]. Moreover, Jo et al…”
Section: Neuroprotective Effects Of Nurr1mentioning
confidence: 99%